Mass Spectrometry Imaging Establishes 2 Distinct Metabolic Phenotypes of Aldosterone-Producing Cell Clusters in Primary Aldosteronism. Issue 3 (March 2020) - Sun, Na; Meyer, Lucie S.; Feuchtinger, Annette; Kunzke, Thomas; Knösel, Thomas; Reincke, Martin; Walch, Axel; Williams, Tracy Ann
Abstract : Aldosterone-producing adenomas (APAs) are one of the main causes of primary aldosteronism and the most prevalent surgically correctable form of hypertension. Aldosterone-producing cell clusters (APCCs) comprise tight nests of zona glomerulosa cells, strongly positive for CYP11B2 (aldosterone synthase) in immunohistochemistry. APCCs have been suggested as possible precursors of APAs because they frequently carry driver mutations for constitutive aldosterone production, and a few adrenal lesions with histopathologic features of both APCCs and APAs have been identified. Our objective was to investigate the metabolic phenotypes of APCCs (n=27) compared with APAs (n=6) using in situ matrix-assisted laser desorption/ionization mass spectrometry imaging of formalin-fixed paraffin-embedded adrenals from patients with unilateral primary aldosteronism. Specific distribution patterns of metabolites were associated with APCCs and classified 2 separate APCC subgroups (subgroups 1 and 2) indistinguishable by CYP11B2 immunohistochemistry. Metabolic profiles of APCCs in subgroup 1 were tightly clustered and distinct from subgroup 2 and APAs. Multiple APCCs from the same adrenal displayed metabolic profiles of the same subgroup. Metabolites of APCC subgroup 2 were highly similar to the APA group and indicated enhanced metabolic pathways favoring cell proliferation compared with APCC subgroup 1. In conclusion, we demonstrate specific subgroups of APCCs with strikingly divergent distribution patterns of metabolites. One subgroup displays a metabolic phenotype convergent with APAs and may represent the progression of APCCs to APAs. Abstract : Supplemental Digital Content is available in the text.